Students' Perception of Blended Learning in Cultural Arts Lesson at SMA Pertiwi 1 Padang - Nindi Aulia Safira; Indrayuda (Universitas Negeri Padang, 2024)
The purpose of this study was to determine students' perceptions of blended learning in dance subjects at SMA Pertiwi 1 Padang. The type of research is qualitative with a descriptive method. The research instrument is the researcher himself, assisted by supporting instruments such as stationery and cameras. The data used are primary and secondary data. The data collection techniques were carried out through observation, interviews, literature study, and documentation. The steps for analyzing data in this study are data reduction, data presentation, and conclusion drawing. The results showed that students' perceptions of blended learning in dance lessons were